Implementasi Teknologi Artifical Intelligence (AI) sebagai Penunjang Pembelajaran Siswa di SMK Nusatama Kota Padang - Yuliawati Yunus; Renny Permata Saputri; Monica Fransisca (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
Community Service (PKM) is one of the tasks of the Tri Dharma of Higher Education which must be fulfilled by lecturers. The PKM activities carried out had the theme Implications of Artificial Intelligence (AI) Technology as a Support for Student Learning. The partner collaborating on this PKM activity is Nusatama Vocational School, Padang City. Initial observations found that the use of Artificial Intelligence (AI) technology was still very lacking. The aim of PKM activities is to introduce Artificial Intelligence (AI) technology to vocational high school students. It is hoped that this PKM activity can increase students' knowledge about Artificial Intelligence (AI) technology, and can raise children's motivation in learning, produce positive attitudes, as well as a strong commitment to learning and a good attitude towards teachers. This service uses presentations and simulations of the introduction and implications of learning Artificial Intelligence (AI) technology for students. Analysis, education and education methods are used in this service by the service implementation team. This PKM activity resulted in an increase in students' knowledge about Artificial Intelligence (AI) technology and its application as a support for student learning.